2018
DOI: 10.1002/pca.2786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artemisiae argyi Folium and Artemisiae lavandulaefoliae Folium by simultaneous determination of multi‐components with single reference standard method and chemometric analysis

Abstract: The single reference standard for simultaneous determination of the multi-components method coupled with chemometrics analysis could be a well-acceptable strategy to compare and evaluate the quality of Artemisiae argyi Folium and Artemisiae lavandulaefoliae Folium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…In order to comprehensively compare the extraction efficiency of DESs and conventional solvents for extraction of phenolic acids from AL, different ratios of methanol (25% MeOH, 50% MeOH, 75% MeOH, and 100% MeOH), efficient solvents commonly used in the extraction of bioactive compounds from natural products, were selected as reference solvents [7]. As shown in Figure 2, among the different ratios of MeOH, 75% MeOH displayed the highest extraction efficiency for the four phenolic acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to comprehensively compare the extraction efficiency of DESs and conventional solvents for extraction of phenolic acids from AL, different ratios of methanol (25% MeOH, 50% MeOH, 75% MeOH, and 100% MeOH), efficient solvents commonly used in the extraction of bioactive compounds from natural products, were selected as reference solvents [7]. As shown in Figure 2, among the different ratios of MeOH, 75% MeOH displayed the highest extraction efficiency for the four phenolic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Although the AL has been used as an herbal medicine and food ingredient for a long time, studies on its bioactive compositions are still limited. Phytochemical studies disclosed that AL contains various bioactive constituents, mainly including volatile oils, phenolic acids, flavonoids, and terpenoids [6,7]. Among bioactive constituents, phenolic acids have been recognized as the main active compounds in AL [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an edible herbal medicine, AL has been widely used in clinic in China and other Asia countries. Our previous studies have shown that polyphenols, including caffeoylquinic acids and flavonoids, are main bioactive constituents in AL, which has been reported to display hypoglycemic and hypolipidemic properties (Guo et al, 2019). However, there is no information about the potential anti-lipase of AL.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of Artemisia argyi H.Lév. and Vaniot (AL), a common herbal medicine for treatment of hemorrhage, dysmenorrhea, abdominal pain eczema and skinitch (Guo et al, 2019), which is mainly distributed in China, Korea, Mongolia, and Japan (Abad et al, 2012). AL is also used as a food ingredient due to its delicious flavor and characteristic smell (Xiao et al, 2019)., AL is consumed as a condiment and colorant for the traditional food "Qingtuan" in China, and AL is also used as an additive in dietary food to enhance the flavor and nutrition in Japan (Abad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%